The concept of modal meaning in the category of negation - Kussaiynova, Ж.А.; Samenova, С.Н. (Bulletin of L.N. Gumilyov Eurasian National University. PHILOLOGY Series, 2023)
Until now, the analysis of linguistic features of the category of subjective modality in combination with the structure of independent sentences prevails in Kazakh linguistics. But in this case, it is obvious that one-sided opinions are formed in the differentiation of a large-scale and complex structural feature of modality, the ambiguity of some grammatical techniques, systematized from intertextual communication. Secondly, the analysis of the creation of internal values of the category of subjective modality based on the works of individual authors is still relevant. Because from the skills of independent writing of each author, we can come to relevant theoretical conclusions that will serve as the basis for understanding the complex and large-scale structure of this pattern. In this scientific article, written on the basis of such premises, for the first time in scientific argumentation, the formation of modal meanings bymeans of the category of negation in Abai’s poetry was laid. Consequently, it becomes clear from real linguistic data that the active use of the methods of the category of negation in the poet’s works is the basis for determining such modal shades as approval, disapproval, protest, remorse. Based on the collected examples, according to the stylistic transformations of the poet, the activity of these shades in the transmission of modal values is classified, sometimes repetition is used, in other cases the opposite meaning is used, and sometimes it is supplemented by a number of synonyms. Conclusions and conclusions in the scientific article contribute to the development of theoretical features of the category of modality, the identification of internal connections and boundaries of certain patterns, a comprehensive study of the grammatical system of the category of modality